## kissme 3 years ago 8x-y+5z from the sum of 2x+3y - 6z and 5x-3y

1. tishara429

13331

2. kissme

pls complete solution :)

3. tishara429

6971

4. Callisto

the sum of 2x+3y - 6z and 5x-3y = (2x + 3y -6z) + (5x - 3y) = 2x + 5x +3y - 3y -6z = 7x - 6z To get 8x-y+5z from the sum of 2x+3y - 6z and 5x-3y, we need to add something. Let that something be A [ (2x + 3y -6z) + (5x - 3y) ] + A = 8x-y+5z ( 7x - 6z ) + A = 8x - y + 5z Subtract both sides by 7x ( 7x - 6z ) + A - 7x = 8x - y + 5z -7x A - 6z = x - y + 5z Add 6z to both sides A - 6z + 6z = x -y + 5z + 6z A = x - y + 11z So, to get 8x-y+5z from the sum of 2x+3y - 6z and 5x-3y, we need to add x - y + 11z.

5. Callisto

I hope I didn't misinterpret the question :(

6. tishara429

yes

7. tishara429

you did fine

8. kissme

THANKS

9. kissme

10. tishara429

15

11. Callisto

12. tishara429

13. Callisto

Do you mind explaining it detailedly? Sorry that I'm slow!

14. tishara429

ok you add the number which equals the answer u got and then you will have the correct answer so thats how you solve the question.

15. Callisto

But there are some unknowns there, you can't add them directly because they are NOT the like terms, right?

16. tishara429

oh i see then u have to divide